Translanguaging and multilingual society of Macau: past, present and future - Johnny F. I. Lam; Wai In Ieong (Asian-Pacific Journal of Second and Foreign Language Education, 2022)
Abstract This paper aims to explore the development and evolution of multilingual languages in Macau over the past 400 years, as well as the relationship and interaction of these languages with Macau society. The complex relationship between translation and society in multilingual societies is also discussed. By doing so, this study attempts to fill the current research gap by investigating the formation and evolution of multilingualism in a multicultural context from a historical perspective. To understand the evolving changes in Macau’s languages and the relationship with society at large, this paper provides a review of the evolution of the multilingual society in Macau from a historical perspective while analyzing the features of Macau's multiple languages in different historical periods and revealing the influence of multilingualism on Macau’s development. This review argues that there are three stages in the formation of a multilingual society and culture in Macau: Chinese as the predominant language in Macau (ancient times-1553), the early introduction of foreign languages and the official status of Portuguese languages in Macau (1553–1987), and Chinese, Portuguese, and English as the three mainstream languages in Macau (1987-present). Through a review of the past for insights into the formation of the multilingual society in Macau, the paper sheds light on the long history of Macau’s Chinese and Portuguese cultures and their main linguistic influence on Macau’s society and culture. Findings reveal that Macau could utilize its Portuguese characteristics and play an influential role in world communications, bridging the gap between China and Portuguese-speaking countries.